Governance of mineral resources: Towards the end of national states’ supremacy? - Fanny Verrax (Etikk i Praksis: Nordic Journal of Applied Ethics, 2014)
This paper addresses the issue of mineral resources’ governance and trading rules. In doing so, it takes a closer look at the 2012 World Trade Organization (WTO) case pertaining to Chinese exportation quotas of rare earth elements and other minerals. It argues that the current governance system based on national responsibility over resources control and global trading rules is not well adapted to a sustainable and fair management of mineral resources, and concludes by suggesting two paths towards a better governance of such resources.